Capillary Flow in a Smart Watering System - Nurdiyanto, Nurdiyanto; Wahyuni, Siti (Indonesian Journal of Advanced Research, 2025)
The use of water in the agricultural sector continues to be carried out to increase demand and availability in an economical and efficient manner. Irrigation is a way to meet plant needs. There are several irrigation systems, including the smart watering system. This system provides water flow from the main reservoir to the plant reservoir through outlet holes and hose channels. Then the water from the plant reservoir is absorbed through the capillary axis. On a household scale, capillary irrigation can be developed. This research was carried out on spinach plants using a treatment design method using two capillary axes by adjusting the water opening and closing system from the main reservoir. The research parameters consisted of water use, water loss and root fresh weight. The research results showed that evaporation occurred every day under normal conditions on days 1 to 10. There was an increase in evaporation on the 12th day until harvest. The main reservoir measures 46 cm long and 31 cm wide. The upper limit of the water level is 13 cm and the lower limit of the water level is 9 cm from the bottom of the main reservoir. The water level condition from day 1 until harvest time decreased by up to 9.8 cm. The fresh weight condition obtained on day 1 was 0 grams, day 13 was 21.23 grams and day 28 (harvest) was 37.12 grams.